The Action of Thrombin on Modified Fibrinogen - Osbahr, A J (Thrombosis and Haemostasis, 1983)
The modification of canine fibrinogen with citraconic anhydride modified the ε-amino groups of the fibrinogen and at the same time generated additional negative charges into the protein. The addition of thrombin to the modified fibrinogen did not induce polymerization; however, the fibrinopeptide was released at a faster rate than from the unmodified fibrinogen. The physical properties of the citraconylated fibrinogen were markedly altered by the modification of 50-60 lysine residues in one hour. A modified fibrinopeptide-A was released by thrombin from the modified fibrinogen and was electrophoretically more anionic than the unmodified fibrinopeptide-A. Edman analysis confirmed the modification of the lysine residue present in the peptide. The rate of removal of citraconylated fibrinopeptide-A from modified fibrinogen by thrombin was 30 to 40 percent greater than the cleavage of unmodified fibrinopeptide-A from unmodified fibrinogen. However, the modification of 60 or more lysine residues in the fibrinogen produced a decrease in the rate of cleavage of citraconylated fibrinopeptide-A. The results suggest that additional negative charge in the vicinity of the attachment of fibrinopeptide-A to canine fibrinogen aids in the removal of the peptide by thrombin.
Keywords: Fibrinogen; Thrombin; Citraconylated fibrinogen; Fibrinopeptide-A; Lysine group